Implementasi Good Governance pada Layanan Terpadu Hubungan Industrial (LTHI) Bidang HI dan Jamsos Disnakertrans Provinsi Jawa Timur - Fauzan Arya Daniswara (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This research discusses the implementation of good governance principles in the Integrated Industrial Relations Service (LTHI) at the Manpower and Transmigration Office of East Java Province. The background of this study is the increasing number of industrial relations disputes, which reached 817 cases in 2024, with termination of employment (PHK) disputes being the most prevalent. The aim of this research is to explore the application of good governance in the context of public services involving workers, employers, and the government. The method used is a qualitative approach with semi-structured interviews and document analysis. The results show that LTHI has implemented principles of transparency, accountability, participation, and responsiveness, although challenges remain in terms of infrastructure and coordination among stakeholders. The conclusion of this research highlights the importance of strengthening mediator capacity and technological support to enhance service effectiveness, as well as the need for better collaboration among all related parties. These findings are expected to provide recommendations for the development of better public service policies in the future.